Implementation of Web Blog-Based E-Learning Media to Improve Students' Response and Interest in Sociology Learning for Class XI IPS 2 - Martina, Martina; Rustiyarso, Rustiyarso; Sulistyarini, Sulistyarini (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study aims to determine the use of Web Blog-based E-Learning media to increase students' responses and interest in learning sociology in class XI IPS2 SMA Negeri 2 Mandor. This study seeks to get clarity regarding student responses in Sociology subjects using Web Blogs. In addition, it also examines the interest in studying sociology after students are taught with Web Blogs. The research method that is suitable for use in this study is the ex-post facto method. Sociology learning Web Blog has been implemented, but the impact has never been measured. This study seeks to reveal the impact caused by Web Blogs used in sociology learning. Sampling was done by means of proportional random (proportional random sampling).The results of this study indicate that the use of Web Blogs in teaching Sociology at SMA Negeri 2 Mandor turns out to have a significant effect on both student responses and interest in studying sociology. The results are in line with the developed conceptual framework. If sociology learning uses Web Blogs, the response and interest of students in learning sociology increases. Based on the results of the data, facts and theories obtained on the use of blog media on learning interest in sociology learning at SMA Negeri 2 Mandor, it can be seen that this can happen for several reasons, including: the media blog is a means, intermediary or message delivery (subject matter) whose reception is through hearing and sight, conveyed from both the teacher and the actual reality.